Genetic analysis of agronomic and fall armyworm-resistance traits in maize hybrids with varying levels of resistance to stem borers (2022)
Stem borer (SB) and more recently, fall armyworm (FAW) are serious economic pests in maize production in sub-Saharan Africa. It is hypothesized that SB-resistant germplasm may confer resistance against FAW. However, the performance of SB-resistant lines in hybrid combinations and the inheritance of FAW-resistant traits under variable FAW infestations have not been reported. This study was conducted to (i) obtain information on the inheritance of agronomic and FAW-resistant traits under variable FAW infestations; (ii) identify hybrids combining high grain yield (GYLD) and stability under FAW infestations; and (iii) determine the effects of FAW damage on GYLD. Three SB-resistant lines (1393, CKSBL10060 and CML 331) as testers and six open-pollinated varieties (OPVs) as lines were crossed in a line tester scheme to generate eighteen test crosses. The test crosses together with two tester x tester crosses and two checks were evaluated under artificial FAW infestation (AI), natural infestation (NI) and pesticide-protected condition (PC) in Nigeria. Additive and nonadditive effects were significant for GYLD, most agronomic and FAW-resistant traits under AI and NI, except ear damage (EDAM) scores under NI, whereas only the non-additive effect was significant for GYLD under PC. Two testers (1393 and CKSBL10060) combined significant and positive GCA effects for GYLD with desirable GCA effects for FAW-resistant traits under AI and NI, whereas CML 331 combined significant and negative GCA effects of GYLD with undesirable GCA effects of FAW resistance under the test conditions. Three OPVs (AWR SYN-W2, AMATZBR-WC4 and TZB-SR) had a significantly positive GCA effect for GYLD and a desirable GCA effect for either leaf damage (LDAM) or EDAM score under AI. The FAW LDAM and EDAM significantly reduced GYLD under AI but not under NI. Three test crosses (AMATZBR-WC4 x CKSBL10060, TZB-SR x CKSBL10060 and TZBR Comp 1-WC2 x 1393) combined high yield with stability and FAW tolerance across the test conditions and thus were recommended for further testing.